Web-based health Information Seeking and eHealth Literacy among College students. A Self-report study - KHademian, Fatemeh; Arshadi Montazer, Mahsa Roozrokh; Aslani, Azam (Investigación y Educación en Enfermería, 2020)
Objective. This study aimed to assess web-based health information seeking and eHealth literacy among Iranian college students. Methods. The study was conducted in five colleges of the Shiraz University of Medical Sciences in Iran during 2018. The data were collected by a researcher-made questionnaire consisting of seven questions on a 4-point Likert-type scale, with scores ranging from 7 to 28. These questions were: ′I know how to use the Internet to answer my questions about health′, ′I think there is enough information about health-related issues on the Internet′, ′I know the vocabulary used in health issues on the Internet′, ′I can tell high-quality health resources from low-quality health resources on the Internet′, ′I know how to use the health information I find on the Internet to help me′, ′I feel confident in using information from the Internet to make health decisions′, and ′Searching for health-related information on the Internet will increase my knowledge in this field′. High eHealth literacy level is defined as above the total mean score and low eHealth literacy level is defined as lower than the total mean score. Results. In all, 386 college students participated in the study. The results showed that the mean score of eHealth literacy was 19.11 out of 28; 205 participants (54.4%) had low eHealth literacy. In addition, the students used the Internet to search for information regarding diseases symptoms (70%), physical illnesses (67.1%), existing treatments (65%), and diagnosis (63.1%). Conclusion. The results showed that participants in this study usually searched for illnesses, symptoms, and treatments after they got sick and paid little attention to other aspects related to integral health. How to cite this article: KHademian F, Roozrokh M, Aslani A. Web-based health Information Seeking and eHealth Literacy among College students. A Self-report study. Invest. Educ. Enferm. 2020. 38(1):e08.